Precipitating or prohibiting factor: Coaches' perceptions of their role and actions in anti-doping. Issue 5 (October 2017) - Allen, Justine B; Morris, Rhiannon; Dimeo, Paul; Robinson, Leigh
Coaches are frequently cited as potentially precipitating or preventing athletes' engagement in doping. However, little is known about coaches' perspectives. Therefore, the purpose of this study was to examine coaches' perceptions of their role and actions in athletes' anti-doping behaviour. Twenty-three coaches (M = 17, F = 6) working with performance athletes in Scotland participated in semi-structured interviews where topics related to doping and anti-doping were discussed. Thematic analysis, guided by Schön's role frame and reflective conversation concepts, was used to develop themes. Analysis led to the development of four internal role frame themes: clean sport value, approach to preparation and performance, responsibility to athletes and knowledge; and five boundary role frame themes: Scottish/British sporting culture, potential for benefit, prevalence of doping and testing, clarity of responsibilities and consequences, and beyond coaches' control. The coaches' role frame supported an anti-doping stance, but, it also presented a risk and was insufficient to ensure action. Analysis of coaches' reflective conversations revealed the issues set by the coaches differed and influenced subsequent actions and evaluations.